Relationship between Indicators of Nutritional Status and the Development of Pneumonia Associated with Ischemic Stroke - Alexis Suárez Quesada; Alexis Álvarez Aliaga; Julia Matilde Pupo Jiménez; Joel Berdú Saumell; Marta Elena Hernández Galano (Revista Finlay, 2020)
Background: malnutrition is a common problem among hospitalized patients. This disease causes severe consequences in the clinical course, increases the risk of infections, among which pneumonia highlight, mortality and hospital stay. Objective: to determine the possible association between the indicators of nutritional status at admission and the development of pneumonia associated with ischemic stroke. Methods: 361 patients belonging to a prospective cohort study with the diagnosis of acute ischemic stroke, admitted consecutively to the stroke room, internal medicine and clinical intermediate therapy of the Carlos Manuel de Céspedes General University Hospital during the first 7 days were studied from their admission, since September 2016 to December 2018. Independent predictors of pneumonia associated with ischemic stroke were obtained using multivariate logistic regression. Results: out of 361 patients, the 21.9 % developed stroke-associated pneumonia, atherothrombotic infarction was the most frequent etiological subtype. The 39.1 % of the patients presented a certain degree of nutritional risk upon admission, the main factors identified were the global lymphocyte count 7 mmol / l and aspartate- aminotransferase> 25 U / L. Conclusions: the initial nutritional status, evaluated using the available nutritional status indicators, has an influence on the development of pneumonia in patients with ischemic stroke.